A graphene-based hybrid material with quantum bits prepared by the double Langmuir–Schaefer method. Issue 42 (2nd August 2019) - Hrubý, Jakub; Santana, Vinicius T.; Kostiuk, Dmytro; Bouček, Martin; Lenz, Samuel; Kern, Michal; Šiffalovič, Peter; van Slageren, Joris; Neugebauer, Petr
Abstract : Graphene-based hybrid material with array of copper(ii )-based quantum bits was prepared by a wet-chemistry protocol and characterised by HF-ESR, XPS, Raman, and AFM. Abstract : The scalability and stability of molecular qubits deposited on surfaces is a crucial step for incorporating them into upcoming electronic devices. Herein, we report on the preparation and characterisation of a molecular quantum bit, copper(ii )dibenzoylmethane [Cu(dbm)2 ], deposited by a modified Langmuir–Schaefer (LS) technique onto a graphene-based substrate. A double LS deposition was used for the preparation of a few-layer-graphene (FLG) on a Si/SiO2 substrate with subsequent deposition of the molecules. Magnetic properties were probed by high-frequency electron spin resonance (HF-ESR) spectroscopy and found maintained after deposition. Additional spectroscopic and imaging techniques, such as Raman spectroscopy (RS), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), and scanning electron microscopy (SEM) were performed to characterise the deposited sample. Our approach demonstrated the possibility to utilise a controlled wet-chemistry protocol to prepare an array of potential quantum bits on a disordered graphene-based substrate. The deployed spectroscopic techniques showed unambiguously the robustness of our studied system with a potential to fabricate large-scale, intact, and stable quantum bits.